Arterial stiffness and lifestyle modification - Asako Miyaki; Seiji Maeda (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Previous research has established that both aging and obesity trigger elevation of arterial stiffness and that such elevation is an independent risk factor for cardiovascular morbidity and mortality. Changes in arterial stiffness are known to be caused by alterations in the balance of hormones, inflammatory, nervous system-related, and endothelium-derived vasoactive factors, and levels of oxidative stress - all of which are known to strongly affect vasoconstriction and vasodilation. Lifestyle modifications that promote the restriction of energy intake, maintenance of nutrient balance, and performance of regular aerobic exercise, can decrease arterial stiffness in elderly and obese individuals. In this review, we discuss the lifestyle strategies found effective in decreasing arterial stiffness in elderly and obese individuals via improvement of vasoactive functional factors.